2013
DOI: 10.1038/nrcardio.2013.60
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of heart failure therapies

Abstract: Heart failure (HF) is a leading cause of morbidity and mortality worldwide. Management of HF involves accurate diagnosis and implementation of evidence-based treatment strategies. Costs related to the care of patients with HF have increased substantially over the past 2 decades, partly owing to new medications and diagnostic tests, increased rates of hospitalization, implantation of costly novel devices and, as the disease progresses, consideration for heart transplantation, mechanical circulatory support, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 125 publications
0
47
0
2
Order By: Relevance
“…Management of HF with pharmacological therapies and implantable device therapy has been studied extensively to prove their clinical effectiveness 43. The ICERs for medical device therapy for HF patients are between US$10 900 and US$303 000/QALY, depending on the intervention considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Management of HF with pharmacological therapies and implantable device therapy has been studied extensively to prove their clinical effectiveness 43. The ICERs for medical device therapy for HF patients are between US$10 900 and US$303 000/QALY, depending on the intervention considered.…”
Section: Discussionmentioning
confidence: 99%
“…Implantable cardioverter defibrillators (ICDs), CRT‐P pacemakers, and CRT‐D defibrillations have been evaluated in the HF population for which these devices are known to have clinical benefit. Cost‐effectiveness studies of ICDs are sensitive to the patient population selected in each individual trial, and ICERs vary from US$34 000 to > US$70 000 per QALY gained over a lifetime 43. ICERs across countries are variable due to variations in healthcare practices and prices.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In general, all analyses have suggested that three key factors drive value for money: battery longevity, duration of benefit, and age at implantation. Obviously, complications add cost to the overall equation.…”
Section: Jennifer Taylormentioning
confidence: 99%
“…1). Moreover, each successive hospitalization carries a higher probability of death [5], and impacts on health economics, due to the high costs of HF-related hospitalization [4,6,7].…”
mentioning
confidence: 99%